1994
DOI: 10.1002/jsfa.2740650412
|View full text |Cite
|
Sign up to set email alerts
|

The use of prilled fat to coat and protect amino acids from ruminal degradation

Abstract: A series of trials was conducted to determine the effectiveness and limitations associated with the use of partially hydrogenated triglycerides as a protective coating to enhance amino acid escape from the rumen. Commercially prepared prills and laboratory-synthesized prills containing either lysine or methionine were incubated from 0-24 h in situ, in a fistulated cow fed hay and grain (1 : 1, w/w DM). Multiple factors were found to affect the ability of fat to protect amino acids. Examination of prill size wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
1
6
0
1
Order By: Relevance
“…Indeed, these surface structure images appear to be in agreement with our previous observation ( Reiners and Brake, 2016 ) that greater acidity increased amounts of lysine lost from lipid-associated lysine mixed with corn silage but that acidity had little impact on amount of lysine lost from lipid-associated lysine mixed with alfalfa silage. Obviously, surface structure images are subjective measures, but these images appear to agree with the report of Ji et al (2016) , our previous observations ( Reiners and Brake, 2016 ) and the conclusions of Block and Jenkins (1994) . Regardless, images from this preliminary study clearly indicate that measures of lysine bioavailability are necessary to allow an improved understanding of amounts of metabolizable lysine provided from lipid-coated lysine after exposure to silage.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Indeed, these surface structure images appear to be in agreement with our previous observation ( Reiners and Brake, 2016 ) that greater acidity increased amounts of lysine lost from lipid-associated lysine mixed with corn silage but that acidity had little impact on amount of lysine lost from lipid-associated lysine mixed with alfalfa silage. Obviously, surface structure images are subjective measures, but these images appear to agree with the report of Ji et al (2016) , our previous observations ( Reiners and Brake, 2016 ) and the conclusions of Block and Jenkins (1994) . Regardless, images from this preliminary study clearly indicate that measures of lysine bioavailability are necessary to allow an improved understanding of amounts of metabolizable lysine provided from lipid-coated lysine after exposure to silage.…”
Section: Resultssupporting
confidence: 86%
“… Block and Jenkins (1994) observed large amounts of lysine loss from lipid-associated lysine during ruminal incubation. These authors ( Block and Jenkins, 1994 ) speculated that lysine associated with the surface of the lysine-lipid particle was rapidly solubilized during ruminal incubation and that diminished surface integrity of the lysine-lipid particle allowed movement of ruminal fluid throughout the lysine-lipid particle. Reduced integrity of the lipid-lysine particle may also allow movement of water throughout the lysine-lipid particle when mixed with diets that contain large amounts of moisture and increase lysine lost from lipid-coated lysine.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Coating protection efficiency is highly dependent on several factors including coating composition, smoothness of pellet surface, and pellet size (Wu and Papas, 1997). Ruminal degradation of the lipid coating of the RPL products may account for some of the observed Lys loss as research assessing the efficacy of prilled fat to protect Lys from ruminal degradation observed a similar effect of time, with Lys recovery being reduced at 6 h and Lys recovery continuing to diminish through 24 h (Block and Jenkins, 1994). This suggests that increased retention time in the rumen leads to increased microbial degradation of the protective coating.…”
mentioning
confidence: 99%
“…método de proteção ruminal utilizado neste experimento, estudo de degradação in situ conduzido porBlock & Jenkins (1994) mostrou que esta resposta pode variar em função da espessura da "cápsula" de gordura envolvendo o que está sendo protegido (e.g. CLA, aminoácido, etc.)…”
unclassified